N95 respirators: quantitative fit test pass rates and usability and comfort assessment by health care workers. Issue 2 (29th May 2022) - Ng, Irene; Kave, Benjamin; Begg, Fiona; Bodas, Charles R; Segal, Reny; Williams, Daryl
Abstract: Objectives: To compare the performance of four N95 respirator types with respect to quantitative fit test pass rate and health care worker‐rated usability and comfort. Design, setting, participants: Health care workers who participated in the respiratory protection program at the Royal Melbourne Hospital, 1 October 2020 – 31 May 2021. Participants underwent quantitative N95 respirator fit testing (at least three of four types: semi‐rigid cup, flat‐fold cup, duckbill, and three‐panel flat‐fold types), and were invited to complete an online usability and comfort assessment for respirators for which their fit test results were passes. Main outcome measures: Fit test pass rate, and user‐rated overall comfort and assessment ratings (five‐point Likert scales), by N95 respirator type. Results: A total of 2161 health care workers underwent quantitative fit testing (women, 1586 [73.4%]; nurses, 1271 [58.8%]). The overall fit test pass rates were 65.0% for the semi‐rigid cup respirators (1029/1583 tests), 32.4% for the flat‐fold respirator (660/2035 tests), 59.2% for the duckbill respirators (2005/3387 tests), and 96.4% for the three‐panel flat‐fold respirator (1876/1946 tests). 378 health care workers completed the comfort and usability survey. Overall comfort and assessment ratings each differed by respirator group ( P  < 0.001); the median overall comfort (4; IQR, 3–4) and overall assessment values (4; IQR, 3–5) were highest for the three‐panel flat‐fold respirator and lowest for the semi‐rigid cup respirators (comfort: 2 [IQR, 1–3]; assessment: 2 [IQR, 2–3]). Conclusions: The three‐panel flat‐fold N95 respirator outperformed the three alternative types with regard to fit test pass rate and user‐rated comfort and usability. To maximise respiratory protection for health care workers, these factors should be considered when making respirator procurement decisions.